Supermode Analysis and Characterization of Triangular Vertical Cavity Surface Emitting Laser Diode Arrays - Nusrat Jahan; Kent D. Choquette (IEEE Photonics Journal, 2023)
We show in simulation and experiment that the coherent coupling of electric fields between elements of a triangular photonic crystal vertical cavity surface emitting laser array can be adjusted into antiguided supermodes with approximately equal injection into each array element. The dominant supermodes are found by a complex waveguide mode simulation and can be identified by the number and arrangement of side-lobes of their Fourier-transformed far-field beam profiles. The supermode with all three elements in-phase is found to possess the minimum central lobe angular divergence. Measurements of the continuous wave coherently coupled properties of photonic crystal triangular arrays, nominally emitting at 850 nm, are compared to our simulations. We show that the array can be adjusted to lase in a desired supermode by varying the injection currents into each element of the array. The optical power confined within the central portion of the in-phase coupled beam is greater than that emitted from a single VCSEL which is advantageous for high-brightness applications.